Microalgae cultivation in palm oil mill effluent (POME) for lipid production and pollutants removal - Cheah, Wai Yan; Show, Pau Loke; Juan, Joon Ching; Chang, Jo-Shu; Ling, Tau Chuan (Elsevier, 2018)
Microalgae cultivation in wastewaters has been identified as the solution for economical microalgae cultivation. This study investigated the feasibility of using POME for Chlorella sp. cultivation to yield biomass and lipids, as it generates massively in Malaysia which ranked world palm oil exporter. The optimal POME concentration and pretreatment strategy were applied to promote biomass and lipid productivities. Chlorella sorokiniana CY-1 attained maximal of 11.21% of lipid content with 2.12 g L−1 of biomass concentration when cultivation in acid-heat pretreated 30% (v/v) POME. This provides relatively higher yield than those reported values on POME. Pretreatment was found effective to enhance biomass productions, as it converts lignin in POME into reducing sugars to serve as the supplement. The pollutants removal efficiencies were 62.07% for TN, 47.09% for COD, and 30.77% for TP. This contributes towards greater feasibility in microalgae cultivation for biofuel productions and as well towards environmental sustainability.